Centella asiatica: Alzheimer's Neuroprotective - Wahyuni, Riska; Suriwahyuni; Saif, Annisa Hazrina; Silitonga, Melva (Talenta Publisher, 2025)
Centella asiatica (CA) in Indonesia is known as gotu kola plant which is known to have many compounds contained in it, such as Asiatic acid, madecassic acid (6-hydroxyacetic acid), asiaticoside, madecassoside, betulinic acid, thankunic acid, and isothankunic acid. This study is to determine the benefits of CA triterpenoid bioactive content and the mechanism of CA as a neuropretective against alzheimer's disease. This research used the literature study method by searching online data on various types of article publications and selected according to the PRISMA method. From the literature collected, it was found that CA has the ability as a neoroprotective against Alzheimer's disease. This is because triterpenoid compounds with the bioactive content of asiaticoside, madecid acid, and asiatic acid play a role in inhibiting the enzyme acetylcholinesterase which can act as a neuroprotective in the brain by reducing ROS production which can then restore mitochondrial dysfunction and can improve nerve function in Alzheimer's disease.